Limitations of the implementation of the concept of sustainable development in a coal mining region (the case of the Kemerovo region - Kuzbass) - Zonova Olga (EDP Sciences, 2021)
A three-pronged approach to sustainable development of coalmining regions, which involves the combination of social stability, economic efficiency and environmental sustainability, is discussed in the article. The factors that restrain the increase in the social well-being of the population and the reduction of the environmental burden are identified in the context of the presented limitations on the implementation of the concept of sustainable development of coal mining territories.